(untitled) (Iranian Journal of Kidney Diseases, 2017)
Foreign body reaction is a tissue response against implanted materials. We described for the first time the eosinophilic peritonitis and foreign body giant cell reaction to dialysis catheter in a nonatopic child on continuous ambulatory peritoneal dialysis. We found tenderness, redness, and swelling without purulent discharge around the peritoneal catheter; increased eosinophil count in cloudy dialysis fluid; and blood and hyperechoic granulomatous formation appearance surrounding the peritoneal catheter on ultrasonography and foreign body giant cell reaction to dialysis catheter in pathologic examination of granulomatous lesionin in our patient. The peritoneal dialysis catheter was removed due to resistance to antibiotic and antihistamine treatments for suspected peritonitis and tunnel infection. Foreign body reaction and eosinophilic peritonitis with eosinophilic cloudy dialysis effluent can exist simultaneously. Foreign body reaction should be considered in the differential diagnosis of exit site and/or tunnel infection. Ultrasonography helps distinguish between foreign body reaction and exit-site or tunnel infection.